Biomonitoring of PAHs by using Quercus ilex leaves: Source diagnostic and toxicity assessment - De Nicola, Flavia; Claudia, Lancellotti; MariaVittoria, Prati; Giulia, Maisto; Anna, Alfani (Atmospheric Environment, 2011)
Quercus ilex L. leaves were sampled at nineteen urban sites and two remote sites in order to evaluate PAH contamination degree. One-, two- and three-year-old leaves were collected and leaf lipid content was measured to investigate the inﬂuence of leaf age and lipids in PAH accumulation. Some PAH diagnostic ratios, such as Ant/Ant þ Phen, Flt/Flt þ Pyr, B[a]A/B[a]A þ Crys and IP/IP þ B[g,h,i]P, were calculated. The results suggest that Q. ilex leaves are effective biomonitors of PAH air contamination: in fact, a great PAH accumulation in leaves from the urban areas, until 30-time higher compared to those from the remote sites, has been observed. At each site, the similar total PAH concentrations in leaves of different age, probably due to a canopy effect, indicate an ability of all leaf age classes to monitor local PAH concentrations in air, remarking practical implications for air biomonitoring. The ﬁndings suggest that PAH adsorption in Q. ilex leaves does not result limited by leaf lipid content. Moreover, this study demonstrates the source-diagnostic potential of Q. ilex leaves, because, in particular, the Flt/Flt þ Pyr and IP/ IP þ B[g,h,i]P ratios indicate vehicular trafﬁc as the main source of PAHs in the urban areas and wood combustion in the remote areas. Moreover, to distinguish biomass combustion source, a promising tracer PAH as DB[a,h]A could be used. The high contribution of DB[a,h]A to total PAH concentrations at the remote sites determines a high carcinogenic potential in this area, similar to that calculated for the urban area where the carcinogenic PAH concentrations in absolute values are often higher.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Carcinogenic PAH; leaf age; Leaf dry weight; Leaf lipid; PAH diagnostic ratio; Toxic equivalent factor

Complex adjustments of photosynthetic potentials and internal diffusion conductance to current and previous light availabilities and leaf age in Mediterranean evergreen species Quercus ilex - NIINEMETS, Ü L. O.; CESCATTI, ALESSANDRO; RODEGHIERO, MIRCO; TOSENS, TIINA (Plant, Cell & Environment, 2006)
Mature non-senescent leaves of evergreen species become gradually shaded as new foliage develops and canopy expands, but the interactive effects of integrated light during leaf formation (QintG), current light (QintC) and leaf age on foliage photosynthetic competence are poorly understood. In Quercus ilex L., we measured the responses of leaf structural and physiological variables to QintC and QintG for four leaf age classes. Leaf aging resulted in increases in leaf dry mass per unit area (MA), and leaf dry to fresh mass ratio (DF) and decreases in N content per dry mass (NM). N content per area (NA) was independent of age, indicating that decreases in NM reflected dilution of leaf N because of accumulation of dry mass (NA = NM MA). MA, DF and NA scaled positively with irradiance, whereas these age-specific correlations were stronger with leaf growth light than with current leaf light. Area-based maximum ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) carboxylase activity (VcmaxA), capacity for photosynthetic electron transport (JmaxA) and the rate of non-photorespiratory respiration in light (RdA) were also positively associated with irradiance. Differently from leaf structural characteristics, for all data pooled, these relationships were stronger with current light with little differences among leaves of different age. Acclimation to current leaf light environment was achieved by light-dependent partitioning of N in rate-limiting proteins. Mass-based physiological activities decreased with increasing leaf age, reflecting dilution of leaf N and a larger fraction of non-photosynthetic N in older leaves. This resulted in age-dependent modification of leaf photosynthetic potentials versus N relationships. Internal diffusion conductance (gm) per unit area (gmA) increased curvilinearly with increasing irradiance for two youngest leaf age classes and was independent of light for older leaves. In contrast, gm per dry mass (gmM) was negatively associated with light in current-year leaves. Greater photosynthetic potentials and moderate changes in diffusion conductance resulted in greater internal diffusion limitations of photosynthesis in higher light. Both area- and mass-based gm decreased with increasing leaf age. The decrease in diffusion conductance was larger than changes in photosynthetic potentials, leading to larger CO2 drawdown from leaf internal air space to chloroplasts (ΔC) in older leaves. The increases in diffusion limitations in older leaves and at higher light scaled with age- and light-dependent increases in MA and DF. Overall, our study demonstrates a large potential of foliage photosynthetic acclimation to changes in leaf light environment, but also highlights enhanced structural diffusion limitations in older leaves that result from leaf structural acclimation to previous rather than to current light environment and accumulation of structural compounds with leaf age.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CO2 drawdown; growth irradiance; leaf age; leaf structure; mesophyll conductance; nitrogen content; photosynthetic capacity

Complex adjustments of photosynthetic potentials and internal diffusion conductance to current and previous light availabilities and leaf age in Mediterranean evergreen species Quercus ilex - NIINEMETS, Ü L O; CESCATTI, ALESSANDRO; RODEGHIERO, MIRCO; TOSENS, TIINA (Plant, Cell & Environment, 2006)
Mature non-senescent leaves of evergreen species become gradually shaded as new foliage develops and canopy expands, but the interactive effects of integrated light during leaf formation (QintG), current light (QintC) and leaf age on foliage photosynthetic competence are poorly understood. In Quercus ilex L., we measured the responses of leaf structural and physiological variables to QintC and QintG for four leaf age classes. Leaf aging resulted in increases in leaf dry mass per unit area (MA), and leaf dry to fresh mass ratio (DF) and decreases in N content per dry mass (NM). N content per area (NA) was independent of age, indicating that decreases in NM reflected dilution of leaf N because of accumulation of dry mass (NA = NM MA). MA, DF and NA scaled positively with irradiance, whereas these age-specific correlations were stronger with leaf growth light than with current leaf light. Area-based maximum ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) carboxylase activity (VcmaxA), capacity for photosynthetic electron transport (JmaxA) and the rate of non-photorespiratory respiration in light (RdA) were also positively associated with irradiance. Differently from leaf structural characteristics, for all data pooled, these relationships were stronger with current light with little differences among leaves of different age. Acclimation to current leaf light environment was achieved by light-dependent partitioning of N in rate-limiting proteins. Mass-based physiological activities decreased with increasing leaf age, reflecting dilution of leaf N and a larger fraction of non-photosynthetic N in older leaves. This resulted in age-dependent modification of leaf photosynthetic potentials versus N relationships. Internal diffusion conductance (gm) per unit area (gmA) increased curvilinearly with increasing irradiance for two youngest leaf age classes and was independent of light for older leaves. In contrast, gm per dry mass (gmM) was negatively associated with light in current-year leaves. Greater photosynthetic potentials and moderate changes in diffusion conductance resulted in greater internal diffusion limitations of photosynthesis in higher light. Both area- and mass-based gm decreased with increasing leaf age. The decrease in diffusion conductance was larger than changes in photosynthetic potentials, leading to larger CO2 drawdown from leaf internal air space to chloroplasts (ΔC) in older leaves. The increases in diffusion limitations in older leaves and at higher light scaled with age- and light-dependent increases in MA and DF. Overall, our study demonstrates a large potential of foliage photosynthetic acclimation to changes in leaf light environment, but also highlights enhanced structural diffusion limitations in older leaves that result from leaf structural acclimation to previous rather than to current light environment and accumulation of structural compounds with leaf age.
Keywords: CO2 drawdown; growth irradiance; leaf age; leaf structure; mesophyll conductance; nitrogen content; photosynthetic capacity